Trends in a recreational fishery for mussels in eastern South Africa, based on postal, telephone and online surveys. (1st September 2019) - Steyn, Erika; Groeneveld, Johan C.; Santos, Jorge; Kruger, Alke; Mselegu, Xolani I.; Schleyer, Michael H.
Abstract: The intertidal brown mussel Perna perna is targeted by recreational and subsistence fisheries in KwaZulu-Natal, South Africa. The recreational mussel fishery is monitored by off-site postal, telephone and online questionnaire surveys, assessed in this study. Trends in fisher avidity (proportion of permit holders that went fishing), mean number of outings undertaken per quarter year and catch per unit effort (CPUE, as numbers of mussels collected per outing) between 2002 and 2015 were investigated, based on survey responses and available permit sales data. Fisher avidity was greater during summer, for fishers <30 y old, and for residents of coastal districts. Spring low tide windows limited the number of outings to an average of 3–4 per quarter, during which most fishers collected close to the allowed daily bag limit of 30 mussels. The CPUE trend was constrained by the bag limit, and censored regression models were unable to trace the relative abundance of mussels at the spatio-temporal scale investigated. Despite low response rates and changes in survey strategy, trends based on off-site survey data were broadly consistent, providing the only long-term record of the fishery. Survey response rates, costs and logistical constraints were compared, to develop an optimal survey strategy. We suggest a mixed-mode strategy, increased use of online resources, greater representativity, improved outreach and feed-back of survey results. On-site information is required to verify data from off-site surveys. Highlights: Questionnaire surveys reported stable catch statistics during the 13-year study. Fishers conducted 3–4 outings per quarter and collected close to the daily bag limit. Fisher avidity (proportion of permit holders active per quarter) was seasonal. Avidity was higher for younger fishers (<30 years old) and coastal residents. Limited recreational time, tide and weather constrained fishing effort (outings).